Lack of Association of ACE2 G8790A Gene Mutation with Essential Hypertension in the Chinese Population: A Meta-Analysis Involving 5260 Subjects - Li, Yan-Yan (Frontiers in Physiology, 2012)
Background: The angiotensin converting enzyme 2 (ACE2) G8790A gene polymorphism has been associated with the susceptibility to essential hypertension (EH), but the results are disputable. Objective and methods: To investigate the relationship between the ACE2 G8790A gene polymorphism and EH, 8 separate studies with 5260 subjects were meta-analyzed. The pooled odds ratio (OR) and its corresponding 95% confidence interval (CI) were calculated by a random effect model. Results: In the ACE2 G8790A gene polymorphism and EH meta-analysis in a Chinese population, no significant association was found between the ACE2 G8790A gene polymorphism and EH (OR: 1.03, 95% CI: 0.87–1.21, P = 0.76). In the stratified analysis by gender, no significant risk was found among men or women. Under a dominant model of inheritance in the female subgroup, the pooled OR for the GG/GA+AA value was 1.01 (95% CI: 0.82–1.25, P = 0.92). Under a recessive model of inheritance in the female subgroup, the pooled OR for the AA/AG+GG value was 0.93 (95% CI: 0.50–1.73, P= 0.83). Conclusions: The current meta-analysis suggested that the ACE2 G8790A gene polymorphism might not be related to the increased EH risk in the Chinese population.